2x+12=90+3x+23

Simple and best practice solution for 2x+12=90+3x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+12=90+3x+23 equation:


Simplifying
2x + 12 = 90 + 3x + 23

Reorder the terms:
12 + 2x = 90 + 3x + 23

Reorder the terms:
12 + 2x = 90 + 23 + 3x

Combine like terms: 90 + 23 = 113
12 + 2x = 113 + 3x

Solving
12 + 2x = 113 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
12 + 2x + -3x = 113 + 3x + -3x

Combine like terms: 2x + -3x = -1x
12 + -1x = 113 + 3x + -3x

Combine like terms: 3x + -3x = 0
12 + -1x = 113 + 0
12 + -1x = 113

Add '-12' to each side of the equation.
12 + -12 + -1x = 113 + -12

Combine like terms: 12 + -12 = 0
0 + -1x = 113 + -12
-1x = 113 + -12

Combine like terms: 113 + -12 = 101
-1x = 101

Divide each side by '-1'.
x = -101

Simplifying
x = -101

See similar equations:

| 30x+3=123 | | 16x+420=-100 | | 7-2=13-3 | | 4(y+3)+7=4y+19 | | 22=5x+7 | | X^3-2x^2+5x-1=0 | | 6+2f=20-3f | | 3(y+6)=2(y+4) | | 18[m+0.44]-16=118 | | 4(3x-8)=16 | | -102+7x=7x+24 | | 2x+x^2-35=0 | | x-3.7=3.5 | | -14(3a+6)=12(6-4a)+12 | | 3(y-7)=21 | | 8x-2=94 | | 2(s+1)=12 | | 8p+3=23 | | 9+7r=13 | | 5+5y=25 | | 4(x-3)=-16-1 | | 15=y-13 | | f-5=8 | | 7x-3=109 | | 25-y=13 | | 9-0.25j=5 | | 2x+5x+3y-y=35 | | 2x+12=3x+23 | | -1.2x-5=-1.0x+1 | | 14x+60=24x | | F(1)=x^58-6x^2+5 | | 6x+4=-2-1 |

Equations solver categories